Modification of Platelet Sulfhydryl Groups - Harbury, C. B; Schrier, S. L (Thrombosis and Haemostasis, 1974)
Sulfhydryl (SH) reagents are known to inhibit platelet aggregation but their effect on the release reaction has not been systematically studied. To delineate the functional effect of penetrating versus nonpenetrating SH inhibitors, we studied primary and secondary aggregation, the collagen and thrombin induced release reaction and clot retraction. Washed human platelets were used to avoid exposing plasma proteins and added reagents to SH inhibitors. We found that 5,5´ dithiobis (2 nitrobenzoic acid) interacted only with superficially-located SH groups which were not essential for either aggregation, the release reaction, clot retraction, or membrane stability. N-ethylmaleimide at low concentrations was found to interact in rapid succession with SH groups essential for aggregation, clot retraction, and the release reaction. Finally, at very much larger concentration, it may have interacted with a structural SH group. P-hydroxymercuriphenyl sulfonate presented a very complex pattern. At low concentrations it appeared to interfere with the free access to the platelet surface of externally-added agents. At higher concentrations, it interacted first with SH groups associated with aggregation, and then with SH groups associated with clot retraction. Finally, it appeared to interfere with structural SH groups, producing a membrane leak of proteins and nucleotides. The release reaction was never specifically inhibited.